Does Artificial Intelligence Make Healthcare More Responsive? An Academic Perspective - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare systems represents one of the most significant technological shifts in modern medicine. The cen...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care